2017
DOI: 10.1097/qad.0000000000001586
|View full text |Cite
|
Sign up to set email alerts
|

The value of point-of-care CD4+ and laboratory viral load in tailoring antiretroviral therapy monitoring strategies to resource limitations

Abstract: Objective To examine the clinical and economic value of point-of-care CD4 (POC-CD4) or viral load (VL) monitoring compared to current practices in Mozambique, a country representative of the diverse resource limitations encountered by HIV treatment programs in sub-Saharan Africa. Design/Methods We use the CEPAC-I model to examine the clinical impact, cost (2014 US$), and incremental cost-effectiveness ratio (ICER, $/year of life saved [YLS]) of ART monitoring strategies in Mozambique. We compare: 1) monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…These findings are consistent with studies that have examined the cost-effectiveness of other POC technologies, such as POC CD4 and viral load assays. [27][28][29][30][31] Studies in sub-Saharan Africa found POC CD4 testing and VL monitoring to be costeffective compared to laboratory-based testing and monitoring in adults despite wide variations in cost, sensitivity/specificity, and care cascade characteristics. 27,28,30,31 However, if POC total cost of ownership (TCO) increased from the base case value of $28 to $60/test, POC EID was no longer the preferred strategy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with studies that have examined the cost-effectiveness of other POC technologies, such as POC CD4 and viral load assays. [27][28][29][30][31] Studies in sub-Saharan Africa found POC CD4 testing and VL monitoring to be costeffective compared to laboratory-based testing and monitoring in adults despite wide variations in cost, sensitivity/specificity, and care cascade characteristics. 27,28,30,31 However, if POC total cost of ownership (TCO) increased from the base case value of $28 to $60/test, POC EID was no longer the preferred strategy.…”
Section: Discussionmentioning
confidence: 99%
“…They expressed that introduction of this POC CD4 assay would improve patient care, which was not a focus of this evaluation; however, other studies have shown improved linkages and earlier ART initiations following the introduction of POC CD4 testing. 10,11,18,19,34 The healthcare workers in this study appreciated the fact that it required minimal training and could be used across all cadres. Relevant documents should be translated into the dominant local language, in this case Kiswahili, particularly when task-shifting occurs to lower cadres that may not have the technical background and language skills to navigate non-local-language user manuals and training guides.…”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care CD4 assays potentially decrease the turnaround time for the reporting of CD4 results, improving linkage to care and, when CD4 is a criteria, increasing timeliness in ART initiation and treatment switches. 10,11,12,14,16,17,18,19 Though findings have shown that healthcare workers are able to perform POC testing for patient care, 20 there is little documentation about the acceptability of the technology among healthcare workers. This study assessed healthcare workers’ acceptance, ease-of-use, and specimen collection preferences for the Pima CD4 assay in the clinical setting in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling studies provide evidence for cost-effective clinic-based VL monitoring [13]. New clinic-based VL using NAAT technologies have been developed, commercialized and implemented in pilot programs in many LMICs to close the gap in access [14][15][16][17]. Clinic-based laboratory instruments provide quantitative or semi-quantitative VL at district-level laboratories or primary health care settings in 90 minutes with modest laboratory infrastructure.…”
Section: Introductionmentioning
confidence: 99%